On fuzzy solution of a linear optimization problem with max-aggregation function relation inequality constraints - Mesiar, Radko; Kouchakinejad, Fateme; Šipošová, Alexandra (Annals of operations research, 2018)
Crisp constraints in the case of linear optimization problem linked to max-aggregation function composition as rule may result in unsatisfactory solution. We propose and discuss a method of getting more feasible solutions, relaxing crisp inequalities/extremes by means of fuzzy sets.